2017
DOI: 10.21608/jacb.2017.38899
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Banana Peel in Reduction of Aflatoxin Toxicity in Rats

Abstract: An experiment was conducted to determine the efficiency of banana peel to reduce the toxic effect of aflatoxins (AFS) in male albino rats. Seventy eight male albino rats were assigned to 13 experimental diets. The first one served as control received basal diet only, the second served as control DMSO (basal diet and 5ml DMSO /kg B.W.) daily, but the third and fourth one were received 1mg and 2mg AFs/ml respectively. The three following groups were received basal diet only supplemented with banana peel in perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Also, these results are in harmony with the study of Abdel-Rahman et al . [ 32 ] who found that the banana peel had a practical role in detoxification of aflatoxins in albino rats due to decrease the levels of AST, ALT, ALK-P in the serum.…”
Section: Resultsmentioning
confidence: 99%
“…Also, these results are in harmony with the study of Abdel-Rahman et al . [ 32 ] who found that the banana peel had a practical role in detoxification of aflatoxins in albino rats due to decrease the levels of AST, ALT, ALK-P in the serum.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the amount of blood creatinine in the treatments of 200 and 400 mg/kg was not significantly different from the control group, indicating that this level of essence did not negatively affect the kidney and vital organs, but the 600 mg/kg treatment was associated with a notable increase in the creatinine content. Studies by Abdel Rahman et al [48] showed that in the case of aflatoxin poisoning in Oreochromis niloticus, fennel essential oils can significantly lower the level of blood creatinine, which was elevated due to poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of AFs extracted from A. flavus fermentation medium as described by Abdel-Rahman et al (2017) was determined using HPLC technique (Agilent 1200 Series U.S.A with column C 18 , Lichrospher 100 RP-18, 5µm×25cm). The mobile phase constituted of water: methanol: acetonitrile (54:29:17, v/v/v) at flow rate of 1ml/min.…”
Section: Determination Of Aflatoxins Concentrationmentioning
confidence: 99%